Cobaan Hidup dalam Al-Qur’an (Studi Ayat-Ayat Fitnah dengan Aplikasi Metode Tafsir Tematik) - Lilik Ummi Kaltsum (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2018)
This paper discusses the trials of life which in the Qur’an are called slander. The dominant meaning of slander is a troublesome ordeal. Bad trials here tend to be collective trials rather than individuals. That is, this word is more often used by a certain group in this case are infidels to attack other groups, namely Muslims. This is because many verses about libel fall during the period of makkiyah. Therefore, the meaning of slander that often appears in the Qur’an is chaos, persecution, assault, murder, kufr, expropriation of wealth and the like. Defamation as a test of one's faith is a sunnatullah that cannot be rejected or avoided by anyone. The quality of one's faith will be seen if it has been faced with various difficulties. To get comprehensive results from this discussion, the authors use the thematic method. This method tries to raise various issues and concepts of the Qur’an which ultimately gain an understanding that refers to a unified view of nature and life.